Program Edukasi Tentang Pengetahuan Konflik Pernikahan Pada Fase Dewasa Awal - Wilda Ansar; Novita Maulidya Djalal; Anggun Amalia; Amalia Seha; Alifiyah Az-Zahra (Communio: Jurnal Pengabdian Kepada Masyarakat, 2022)
Living life after marriage is difficult; new roles and adjustments must be made. This program aims to help provide education and get to know the picture of life in marriage and conflicts that may occur to prospective couples who are about to get married and have just undergone two years of marriage. Education is carried out through videos and explanations related to marital conflicts. The data collection method was carried out through a survey using Google Forms. This survey contains open questions that are given before the provision of education/pre-test and after receiving education/post-test. Based on the results of the data analysis, it was found that there was an increase in the knowledge of participants in the marriage conflict education program. This program is expected to have implications for prospective spouses and married couples to be able to deal with marital conflicts with practical problem-solving, and this program is also likely to contribute to reducing the divorce rate in the community.